Assessing the effect of shape on the evaluation of expected and actual chocolate flavour. Issue 1 (December 2017) - Wang, Qian; Reinoso Carvalho, Felipe; Persoone, Dominique; Spence, Charles
Abstract Background Shape can play an important role in our perception of food. In this study, the consequences of crossmodal correspondences between shape and taste on the expected and actual experience of eating chocolate were evaluated. Participants were given two identical dark chocolates differing only in terms of their shape (round or angular) and then rated their expectations of sweetness, bitterness, creaminess and liking. Subsequently, they rated their experience of those attributes on tasting the chocolates. Repeated-measures multivariate analyses (RM-MANOVA) of variance were conducted to assess the role of chocolate shape and cacao content on expected and post-taste chocolate ratings. In addition, we assessed the differences between expected and post-taste ratings for each chocolate shape. Results The results revealed that the shape of the chocolate significantly influenced expected sweetness, bitterness and creaminess. By contrast, it had no significant effect on post-tasting ratings. The round chocolates were judged to be less sweet, more bitter, less creamy and liked less than expected, whereas the angular chocolates were judged to be slightly more creamy than expected. Conclusions The theory of assimilation and contrast is outlined as one plausible mechanism behind the differences between expectation and the actual taste experience. Implications for food product design and directions for future research are discussed.